v.27 - "Keynes, John Maynard" (New Delhi, 2013)
Between the outbreak of war in 1939 and his death in April 1946, Keynes was closely involved in the management of Britain's war economy and the planning of the post-war world. This volume, the sixth dealing with this period, focuses on several aspects of post-war planning: the discussions surrounding relief and reconstruction, the attempts to produce a post-war scheme to stabilise the prices of primary products, and the discussions surrounding Britain's programme of reconstruction, most notably the Beveridge programme for social insurance and the policy of full employment. It contains Keynes's contributions to the discussion of these issues, most notably his primary product scheme and his longer papers on the tactics and problems of a full employment policy.
Keywords: Keynesianism